Development of a 4-NQO toxic equivalency factor (TEF) approach to enable a preliminary risk assessment of unknown genotoxic compounds detected by the Ames II test in UV/H2O2 water treatment samples. (February 2016) - Martijn, Bram J.; Van Rompay, An R.; Penders, Eric J.M.; Alharbi, Yousif; Baggelaar, Paul K.; Kruithof, Joop C.; Rietjens, Ivonne M.C.M.
Abstract: An approach to enable a preliminary risk assessment of unknown genotoxic compounds formed by MP UV/H2 O2 treatment of nitrate rich water, is described. Since the identity and concentration of specific genotoxic compounds is not established yet, a compound specific risk assessment cannot be performed. This limitation is circumvented by introducing a toxic equivalency factor, converting the concentration of unknown genotoxic compounds expressed by an Ames II test response into equivalent concentrations of 4-nitroquinoline oxide (4-NQO), to enable a preliminary risk assessment. Based on the obtained 4-NQO equivalent concentrations for the tested water samples and 4-NQO carcinogenicity data, an indication of the associated risk of the by MP UV/H2 O2 treatment produced nitrated genotoxic compounds is obtained via the margin of exposure (MOE) approach. Based on a carcinogen study by Tang et al. (2004), a body weight of 70 kg and a drinking water consumption of 2 L per day, the 4-NQO equivalent concentration should not exceed 80 ng/L associated with a negligible risk. Application of this approach on samples from MP UV/H2 O2 treated water of a full scale drinking water production facility, a 4-NQO equivalent concentration of 107 ng/L was established. These results indicate a safety concern in case this water would be distributed as drinking water without further post treatment. Highlights: Formation of genotoxic compounds by MP UV/H2 O2 treatment of nitrate rich water. Quantification of unknown genotoxic compounds, applying a Toxic Equivalency Factor. Bench mark dose modelling of in vivo tumour data of 4-NQO. Indications of a safety concern by applying the Margin of Exposure methodology.